Ananalysis of interrelation between motivational components and psychology and educational characteristic of engineering students studying foreign languages - Kravets, O. (Problems of Engineer-Pedagogical Education, 2018)
The paper shows the practice analysis of professional and studying motivation that influence for the activation of students’ practical skill when they study foreign languages. The most meaningful motivational components are defined by the method of sociological poll of first and second year students. The types of psychological motivation are lighted. The interrelation between the students’ psychological characteristics, types of their motivations and influence this connection on students’ activity is established. The kinds of academic activities in the higher educational establishment which will give the possibility to motivate students for studying subject and realize its necessity in the future professional activity are suggested.